Espacios de recreación infantil para desarrollar las relaciones con el medio natural de los niños y niñas del nivel inicial del centro educativo Domingo Savio periodo septiembre 2013-julio 2014 - Parra Cajas, Paola María (2015)
The present research work, denominated "Children's recreation areas to develop relationships with the natural environment of the children on the initial level of the educational center "Domingo Savio" Period September 2013-July 2014 has been structured and developed in accordance to Regulation of the Academic Regime of the Universidad Nacional de Loja .Investigate the theoretical foundation of the spaces of child recreation and of relations with the natural environment of children. Identify the difficulties in relations with the natural environment posed by children. Formulate a guide of organization of spaces of child recreation for develop relations with the natural environment of children. Apply the organizational guide of spaces of child recreation for develop relations with the natural environment of children. Validate the relevance of the guide to organizing spaces recreation of children on the initial leve .For the process of research methods were used: analytical, dialectical, synthetic, and descriptive. The techniques used were as follows; survey of the teaching of the initial level the school "DOMINGO SAVIO", observation sheet applied to children on the initial level that allowed them to diagnose the problems of children and then assess the organizational guide of children’s recreation spaces to develop relationships with the natural environment. Among the main results of the research can be described that the alternative proposal that was applied to solve problems in children was highly effective, the activities implemented within the recreation areas helped reduce the difficulties faced by children about the identification the time, identification of the environment and recognize and differentiate elements of the natural environment, moreover implemented activities prompted the teacher to implement them in the teaching-learning process and thus acquire significant learning in their students.